Reception/Bevakning/Kritik - Isabelle Daunais; Sten Wistrand; Christian Lenemark; Claudia Lindén; Mia Österlund; Birgitta Johansson (Tidskrift för Litteraturvetenskap, 2007)
Isabelle Daunais om Sara Danius, The Prose of the World